Spliced isoforms of the cardiac Nav1.5 channel modify channel activation by distinct structural mechanisms - Mancino, Adamo S.; Glass, William G.; Yan, Yuhao; Biggin, Philip C.; Bowie, Derek (The Journal of general physiology, 2022)
Alternative splicing is an important cellular mechanism that fine tunes the gating properties of both voltage- and ligand-gated ion-channels. The cardiac voltage-gated sodium channel, Nav1.5, is subject to alternative splicing of the DI S3–S4 linker, which generates two types of channels with different activation properties. Here, we show that the gating differences between the adult (mH1) and neonatal (Nav1.5e) isoforms of Nav1.5 are mediated by two amino acid residues: Thr/Ser at position 207 and Asp/Lys at position 211. Electrophysiological experiments, in conjunction with molecular dynamics simulations, revealed that each residue contributes equally to the overall gating shifts in activation, but that the underlying structural mechanisms are different. Asp/Lys at position 211 acts through electrostatic interactions, whereas Thr/Ser at position 207 is predicted to alter the hydrogen bond network at the top of the S3 helix. These distinct structural mechanisms work together to modify movement of the voltage-sensitive S4 helix to bring about channel activation. Interestingly, mutation of the homologous Asp and Thr residues of the skeletal muscle isoform, Nav1.4, to Lys and Ser, respectively, confers a similar gating shift in channel activation, suggesting that these residues may fulfill a conserved role across other Nav channel family members.